2017
DOI: 10.1002/cam4.1287
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: novel applications of nonsteroidal anti‐inflammatory drugs for primary cancer

Abstract: In eukaryotic cells, autophagy is a process associated with programmed cell death. During this process, cytoplasmic proteins and organelles are engulfed by double‐membrane autophagosomes, which then fuse with lysosomes to form autolysosomes. These autolysosomes then degrade their contents to recycle the cellular components. Autophagy has been implicated in a wide variety of physiological and pathological processes that are closely related to tumorigenesis. In recent years, an increasing number of studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 92 publications
3
36
0
Order By: Relevance
“…Numerous studies have indicated that autophagy can be mediated by various pathways, including PI3K/AKT/mTOR, AMPK/mTOR, MAPK/ERK1/2, P53/DRAM and HGF/MET . Among these pathways, the AMPK/mTOR signaling pathway plays a vital role in the process of autophagy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have indicated that autophagy can be mediated by various pathways, including PI3K/AKT/mTOR, AMPK/mTOR, MAPK/ERK1/2, P53/DRAM and HGF/MET . Among these pathways, the AMPK/mTOR signaling pathway plays a vital role in the process of autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…AMPK is a cellular energy sensor that regulates homeostatic balance. It positively regulates autophagy by inhibiting the activity of mTORC1 through direct phosphorylation of its receptor, a regulatory‐associated protein of mTOR …”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, believe that CX-PC-casein-NPs show potential as a formulation for the intravenous administration of CX to treat cancer, since PC and caseins are safe for patients. CX is commercially used in many countries and is commonly administered two or three times (200 mg/time) a day to treat arthritis, menstrual pain, and chronic pain [29]. However, it exhibits poor solubility and variable absorption, which can lead to severe toxicity [14].…”
Section: The Inhibition Effect Of Cx-pc-casein-nps On Tumor Growthmentioning
confidence: 99%
“…The inhibition of mTOR phosphorylation mediated by AMPK phosphorylation can induce autophagy in many different cell types. 15,16 Metformin is a widely used antidiabetic drug used to treat patients with type 2 diabetes mellitus. Studies have shown that it can exert protective effects against cardiovascular diseases; specifically, metformin can activate autophagy and provide cardioprotective effects in δ-sarcoglycan-deficient hearts.…”
Section: Introductionmentioning
confidence: 99%